2012
DOI: 10.1111/j.1469-1795.2012.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of local amphibian populations: modelling the migratory capacity of radio‐tracked natterjack toads

Abstract: The delimitation of the spatial equivalent of isolated populations or interacting sets of local populations is crucial for conservation management. In Amphibia, spatial organization in metapopulations requires knowledge on the individual variation of annual migratory capacity within local populations to delimit core habitats around the breeding site and to estimate the connectivity among neighbouring populations. The migratory behaviour of 143 adult Bufo calamita was monitored using radio‐telemetry at eight lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…These results have been supported in studies about migratory ranges carried out in populations from Britain, which considered that these populations cannot maintain connectivity of neighboring local populations (Sinsch et al. ). On the contrary, metapopulation dynamics seem to be much greater in populations from the Iberian Peninsula (Sinsch et al.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These results have been supported in studies about migratory ranges carried out in populations from Britain, which considered that these populations cannot maintain connectivity of neighboring local populations (Sinsch et al. ). On the contrary, metapopulation dynamics seem to be much greater in populations from the Iberian Peninsula (Sinsch et al.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, connectivity of local populations by dispersers is great in the Iberian Peninsula indicating a considerably large metapopulation system (Sinsch et al. ). The differentiation among natterjack toad populations is only remarkable in fragmented habitats where populations are isolated (Allentoft et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the few available comparable studies, this process of colonization has been suggested in Suaeda maritima , a halophyte plant species that repeatedly colonized former potash mining dumps in Germany (Prinz et al., ; see also Esfeld et al., ). In our case study, B. calamita is known to be a pioneer species with high dispersal capabilities (Miaud, Sanuy, Avrillier, Sanuy, & Miaud, ; Sinsch, Oromi, Miaud, Denton, & Sanuy, ). Thus, the most parsimonious hypothesis is that toads successfully dispersed from natural populations initially established in former semi‐natural habitats (humid meadows or pastures) located in the vicinity of the coalfields (Godin, ).…”
Section: Discussionmentioning
confidence: 99%
“…They will, on one hand, not be able to oversee longer routes, such as pond to pond dispersals, but may make well-informed decisions on the basis of the local environment they find themselves in. As data on individual paths are rare for amphibians and may refer to migration rather than dispersal, it is not possible to confirm whether dispersal routes are informed or naïve (Mazerolle and Vos 2006;Vos et al 2007;Sinsch et al 2012;Sinsch 2014). As a consequence, it is necessary to explore both options (Decout et al 2012).…”
Section: Introductionmentioning
confidence: 99%